The Influence of Brand Image and Price Perceptions on Purchasing Decisions for Wardah Sunscreen Products (Study on Students in Bandung City) - Desfitriady; Hardianti; Erpurini, Wala (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to determine the brand image, price perceptions, and purchasing decisions, and to determine the extent to which brand image and price perceptions influence, both partially and simultaneously purchasing decisions for Wardah sunscreen products for college students in the city of Bandung. The research methods that will be used in this research are a descriptive method and an associative method. In this study, the unit of analysis was individuals, namely students in the city of Bandung who used and purchased Wardah sunscreen products. The sample in this study was 100 people. In this study, the sampling technique used was a non-probability technique with a purposive sampling approach. This study uses multiple analysis methods. From the results of this study, it was seen partially with the significance that there was no effect of brand image on purchasing decisions for Wardah sunscreen products for students in the city of Bandung with a significance value of 0.420 and a magnitude of influence of 2.69%. The price perception variable influences the decision to purchase Wardah sunscreen products for students in the city of Bandung with a significance value of 0.000 and a magnitude of influence of 21.2%. Furthermore, it is seen simultaneously with the significant results that there is an influence of brand image variables and price perceptions on the variable purchase decision of Wardah sunscreen products for students in the city of Bandung with a significance value of 0.000 and a magnitude of influence that is equal to 23.9%.